Better safe than sorry? The effect of trust on venture capitalists' choice of syndicate partners. (1st August 2019) - Plagmann, Carolin; Lutz, Eva
This study investigates the impact of trust among nations on the formation of multinational venture capital syndicates. The data set is based on ThomsonONE and comprises 859 realised triads among lead venture capitalists, their syndicate partners, and portfolio firms. We find that bilateral trust has a significant positive impact on the probability of cooperation in a syndicate. The magnitude of this relationship depends on the status of venture capital markets. The relevance of bilateral trust to the probability of cooperation increases for investments in large venture capital markets with high deal numbers. In line with previous findings on venture capitalists' constricted scrutiny in boom phases, we find that trust becomes less relevant for cooperation during upswings of deal activity in the target market. Consistent with research that finds access to capital as one major reason for syndication; recent capital abundance in the syndicate partner's market reduces the impact of bilateral trust on the probability of cooperation.